Factors impacting antimicrobial resistance in the South East Asian food system and potential places to intervene: A participatory, one health study - Lambraki, I.A.; Mohan, Chadag V.; Cousins, M.; Graells, T.; Léger, A.; Henriksson, Patrik J.G.; Troell, Max F.; Harbarth, S.; Wernli, D.; Jørgensen, P.S.; Carson, C.A.; Parmley, E.J.; et al. (Frontiers Media, 2023)
Background: With AMU projected to increase, South East Asia (SEA) is at high risk of experiencing disproportionate health, social, and economic burdens due to antimicrobial resistance (AMR). Our objective was to identify factors influencing AMR in SEA’s food system and places for intervention by integrating the perspectives of experts from the region to inform policy and management decisions.